Gerakan Literasi Masyarakat melalui Terapi Membaca dan Menulis untuk Mencegah Demensia pada Lansia - Kusumaningtiyas, Tiara; Handayani, Nur Septia; Harisanty, Dessy (Universitas Pahlawan Tuanku Tambusai, 2026)
Based on data for 3 years, from 2017 to 2019, the coverage of elderly health services in the Blora district has fluctuated. Some elderly people in Randublatung District do not have good cognitive or psychomotor routines, so they are prone to Dementia, due to lifestyle or declining health. This Community service activity aims to provide counseling about dementia to the elderly to recognize, understand, and prevent the impact of Dementia. The implementation of the information literacy program through the Community Literacy Movement, with reading and writing therapy to train the brain function of the elderly, such as Crossword Puzzles and True / False games, is designed to adjust the counseling material on Dementia. The activity was carried out in 2 stages: the first was a survey, the second was counseling and evaluation. Participants consisted of 68 people with an average age of 63 years. Participants completed a pretest and posttest about knowledge and attitudes towards Dementia. The results of the activity were an increase in participants' knowledge about dementia by 29.7%, knowledge about literacy by 38.2% and changes in attitudes towards dementia and literacy increased by an average of 58.6%.